2008
DOI: 10.1128/aem.02419-07
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Biofilm-Associated Protein (BapL) May Contribute to Surface Attachment of L. monocytogenes but Is Absent from Many Field Isolates

Abstract: Listeria monocytogenes is a food-borne pathogen capable of adhering to a range of surfaces utilized within the food industry, including stainless steel. The factors required for the attachment of this ubiquitous organism to abiotic surfaces are still relatively unknown. In silico analysis of the L. monocytogenes EGD genome identified a putative cell wall-anchored protein (Lmo0435 [BapL]), which had similarity to proteins involved in biofilm formation by staphylococci. An insertion mutation was constructed in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 38 publications
(27 reference statements)
1
47
1
Order By: Relevance
“…In another study, Zhou et al (48) successfully identified 47 proteins that were either up-or down-regulated in bacteria in the biofdm state. This coordinated gene expression includes the production of regulators associated with the response to stress, the expression of motility genes, the production of biofilm-associated proteins and proteins related to cell-cell communication pathways, and polysac charide biosynthesis (15,16,19,21,37,39). In contrast, a rich culture medium such as TSB supports bacterial growth and biofilm formation but contains biological macromol ecules likely to produce conditioning films, as the present study clearly shows with TSB-coated PS.…”
Section: Discussioncontrasting
confidence: 40%
“…In another study, Zhou et al (48) successfully identified 47 proteins that were either up-or down-regulated in bacteria in the biofdm state. This coordinated gene expression includes the production of regulators associated with the response to stress, the expression of motility genes, the production of biofilm-associated proteins and proteins related to cell-cell communication pathways, and polysac charide biosynthesis (15,16,19,21,37,39). In contrast, a rich culture medium such as TSB supports bacterial growth and biofilm formation but contains biological macromol ecules likely to produce conditioning films, as the present study clearly shows with TSB-coated PS.…”
Section: Discussioncontrasting
confidence: 40%
“…Putative adaptons in the comK prophage may encode similar adhesins that mediate specific attachment to different foodconditioning films. While such adaptons would probably not fully explain attachment and biofilm formation by L. monocytogenes, as many adhesins are chromosomally encoded (7,51), they may help to explain the persistence of specific L. monocytogenes prophage types in individual food processing plants that manufacture the same food product over an extended period of time (5,70,86) (Fig. 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several BapL-negative strains showed higher adherence levels than BapL-positive strains. Collectively, these data suggest that in L. monocytogenes, BapL is neither an essential factor influencing adhesion to surfaces nor is it required for virulence in vivo (Jordan et al, 2008). In marked contrast to all other bacteria possessing a Bap homologue (Lasa & Penadés, 2006), the role of BapL in the course of sessile development could not be established as a reduced level of adhesion did not prevent the formation of a biofilm by the bapL mutant.…”
Section: Biofilm-associated Protein L (Bapl)mentioning
confidence: 74%
“…A homologue of the biofilm-associated protein (Bap) was recently identified in L. monocytogenes and was named BapL (Lmo0435) (Jordan et al, 2008). Among the 43 LPXTG proteins identified to date in L. monocytogenes, BapL is the only one characterized as playing a role in adhesion to abiotic surfaces.…”
Section: Biofilm-associated Protein L (Bapl)mentioning
confidence: 99%